Fatty acid composition of birds and game hunted by the Eastern James Bay Cree people of Québec. Issue 1 (31st January 2016) - Proust, Francoise; Johnson-Down, Louise; Berthiaume, Line; Greffard, Karine; Julien, Pierre; Robinson, Elizabeth; Lucas, Michel; Dewailly, Éric
Abstract : Background: Indigenous peoples have traditionally relied on foods hunted and gathered from their immediate environment. The Eastern James Bay Cree people consume wild game and birds, and these are believed to provide health as well as cultural benefits. Objective: To determine the fatty acid (FA) composition of traditional game and bird meats hunted in the Eastern James Bay area. Design: Harvested traditional game and birds were analysed for FA composition. A total of 52 samples from six wildlife species were collected in the areas of Chisasibi, Waswanipi and Mistissini, of which 35 were from birds (white partridge and Canada goose) and 17 were from land animals (beaver, moose, caribou and black bear). Results: Alpha-linolenic acid (ALA) was the most common n-3 polyunsaturated fatty acid (PUFA) in all samples except for the black bear flesh, in which it was docosapentaenoic acid (DPAn-3). In white partridge, beaver and caribou flesh, PUFAs (mainly n-6) were the most common category of fats while in goose, moose and black bear flesh, monounsaturated fatty acids (MUFAs) predominated. In all species, saturated fatty acids (SFAs) were the second most important FAs. It would appear that in the land animals and birds that were analysed, the SFA content was lower and the PUFA content was higher than store-bought meats giving them a more heart-healthy profile. Conclusions: These results showed that the FA composition of game species consumed by the James Bay Cree population is consistent with a beneficial diet and that traditional foods should continue to be promoted among the Cree people to provide better physical health as well as social and spiritual benefits.